SYNCRIP controls miR-137 and striatal learning in animal models of methamphetamine abstinence - Kim, Baeksun; Tag, Sung Hyun; Nam, Eunjoo; Ham, Suji; Ahn, Sujin; Kim, Juhwan; Cho, Doo-Wan; Lee, Sangjoon; Yang, Young-Su; Lee, Seung Eun; Kim, Yong Sik; Cho, Il-Joo; et al. (Elsevier BV, 2022)
Abstinence from prolonged psychostimulant use prompts stimulant withdrawal syndrome. Molecular adaptations within the dorsal striatum have been considered the main hallmark of stimulant abstinence. Here we explored striatal miRNA-target interaction and its impact on circulating miRNA marker as well as behavioral dysfunctions in methamphetamine (MA) abstinence. We conducted miRNA sequencing and profiling in the nonhuman primate model of MA abstinence, followed by miRNA qPCR, LC-MS/MS proteomics, immunoassays, and behavior tests in mice. In nonhuman primates, MA abstinence triggered a lasting upregulation of miR-137 in the dorsal striatum but a simultaneous downregulation of circulating miR-137. In mice, aberrant increase in striatal miR-137-dependent inhibition of SYNCRIP essentially mediated the MA abstinence-induced reduction of circulating miR-137. Pathway modeling through experimental deduction illustrated that the MA abstinence-mediated downregulation of circulating miR-137 was caused by reduction of SYNCRIP-dependent miRNA sorting into the exosomes in the dorsal striatum. Furthermore, diminished SYNCRIP in the dorsal striatum was necessary for MA abstinence-induced behavioral bias towards egocentric spatial learning. Taken together, our data revealed circulating miR-137 as a potential blood-based marker that could reflect MA abstinence-dependent changes in striatal miR-137/SYNCRIP axis, and striatal SYNCRIP as a potential therapeutic target for striatum-associated cognitive dysfunction by MA withdrawal syndrome. (C) 2022 Chinese Pharmaceutical Association and Institute of Materia Medica, Chinese Academy of Medical Sciences. Production and hosting by Elsevier B.V.